Morphological and Syntactic Errors of Negative Language Transfer from Indonesian in Learning English - Rizki Gunawan, (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2025)
The research explores the impact of negative language transfer on English acquisition among Indonesian learners, based on data from narrative essays written by English Literature students at Universitas Pamulang. The study identifies and categorizes 20 error samples made during the learners’ English development from childhood through secondary education. These errors, traced to the influence of Bahasa Indonesia, are classified into four main types: lexical errors (e.g., incorrect collocations such as make photo instead of take a photo), morphological errors (e.g., subject-verb agreement issues such as They goes), syntactic errors (e.g., word order and missing auxiliaries as in She beautiful is), and pragmatic errors (e.g., culturally inappropriate or overly formal expressions like We are forbidden). Using theoretical support from Odlin’s Transfer Theory, Selinker’s Interlanguage Theory, Krashen’s Input and Monitor Hypotheses, Lado’s Contrastive Analysis, and Vygotsky’s Sociocultural Theory, the research reveals how structural, lexical, and cultural features of L1 are transferred into English. Internal factors such as overgeneralization, developmental gaps, and interlanguage patterns, along with external factors like translation-based instruction and limited exposure to authentic English, contribute to these persistent errors. The study emphasizes the need for targeted pedagogical strategies, including explicit contrastive instruction, increased comprehensible input, and pragmatic competence development, to mitigate the influence of negative transfer and improve learner accuracy and fluency in English.